β-SITOSTEROL FROM Hymenocardia acida root extrac AND ITS ANTIMICROBIAL ACTIVITY - R. Y. Shimbe; T. A. Tor-Anyiin; Md. Zahirul Islam Khan; J. V. Anyam (J. Chem. Soc. Nigeria, Vol. 41, No. 1, pp 76-81 [2016], 2016)
Based on its ethnomedicinal importance and previous report, root extracts of Hymenocardiaacida was investigated in vitro for their antimicrobial activity. Dried, pulverized roots of H. acida were successively extracted via Micro-wave Assisted Extraction (MAE) with hexane, ethyl acetate and methanol.Hexane, ethylacetate and methanol extracts showed sensitivity against Staphylococcus aureus, Streptococcuspyogens, Methicillin – resistant Staphylococcus aureus (MRSA), Bacillus subtilis, Escherichia coli, Klebsiella pneumoniae, Candida tropicalis, Candida stellatoidea. Minimum Inhibitory (MIC), Minimum Bactericidal (MBC) and Minimum Fungicidal Concentrations (MFC) were carried out on the various extracts using tube dilution technique. Graded concentrations of extract solutions in Mueller Hinton and Sabouraud dextrose agar were used to test for bacteria and fungi, respectively. The most active ethyl acetate extract was further separated using Vacuum Liquid chromatography. Collected fractions (sixty) were monitored via thin layer chromatography (TLC) and similar fractions were combined. Combined fraction R-19 gave colourless needle shaped solid (melting point, 136-140 0 C).Comparison of1 H-NMR data with literature reports led to the conclusion that this solid was probably β-sitosterol, C29H50O. This may be the first compound to be isolated and so identified from the roots of this plant. The antimicrobial study of this work justifies and supports traditional use ofHymenocardiaacida in the treatment of various bacteria related ailments